Hubungan Antara Penilaian Anak Terhadap Cerita Film Anak di Televisi dengan Kemampuan Empati Pada Anak Usia Sekolah Dasar - Ratna Sesotya Wedadjati (Unisia, 2009)
This research aims at examining a correlation between judgment of children film on televisionand empathy ability. Samples of this research are ninety three (N=93) children ofelementary school, age between nine to twelve years old in SDN Ngetal Sleman. Instrumentsused are judgment of children film on television and empathy ability scales. Dataare analyzed using the correlation analysis of product moment program based on theSPSS for Windows 13 release. Statistical test reveals that there is significant correlationbetween the level of judgment of children film on television and empathy ability (r=0.382;p=0.000 or p<0.01).Keywords: judgment, children film, television, empathy ability.